Exercise motivation in patients with heart failure. (25th November 2020) - Klompstra, L; Jaarsma, T; Stromberg, A; Van Der Wal, M.H.L
Abstract: Background: Being physically active is important for patients with heart failure (HF) to improve clinical outcome, however, adherence to exercise is low (<50%). To tailor intervention that increase physical activity, it is important to know what motivates HF patients to exercise. Therefore, the aim of the study is to describe motivations of HF patients to exercise and describe variables that are related to their exercise motivation. Methods: This is a cross-sectional analysis of baseline data of 605 patients with HF (mean age 67±12, 71% male, 60%NYHA I/II) who were included in the HF-Wii study. Stepwise regression modelling was used with exercise motivation as dependent variable. Exercise motivation was measured with the Exercise Motivation Index, including 15 statements with answers ranging from 0 (not important) to 4 (extremely important), with 3 subscales (physical, psychological and social motivation). Based on previous research the following predictors were included in the model: quality of life (MLwHFQ), self-efficacy (Exercise self-efficacy scale), cognition (MoCA), depression (HADs), sleeping difficulties (MISS), HF symptoms (fatigue, shortness of breath), age, gender, NYHA-class, comorbidity and educational level. Results: Mean total motivation to exercise was 2.3±0.9 and physical and psychological motivation were rated as the more important (2.7±0.9 and 2.5±0.9) than social motivation (1.8±1.1). Motivation statements that were considered extremely important were being healthier (55% rated 4), slow down the ageing process (38% rated 4) and increasing well-being (31% rated 4). From the multiple linear regression model lower quality of life (β=−0.31, P<0.0001), lower self-efficacy (β=0.16, P<0.0001), experiencing shortness of breath (β=−0.28, P<0.0001), having COPD (β=−0.14, P=0.001) and low educational level (β=−0.09, P<0.028) were predictors related to lower motivation. This model explained 17% of the exercise motivation variability (p<0.0001). Cognition, sleeping difficulties, age, gender, NYHA-class and experiencing fatigue were not significantly related to motivation. Conclusion: Lower quality of life, lower self-efficacy, experiencing shortness of breath, having COPD and lower educational level, decreases the motivation to exercise and may therefore be considered as barriers for exercise. These barriers should be assessed and considered when motivating patients to become more physically active. Funding Acknowledgement: Type of funding source: None